A new species of Phyllotetranychus (Acari: Tenuipalpidae) from Iran - Mahdavi, Sayed Mosayeb; Latifi, Malihe; Asadi, Mahdieh (Zootaxa, 2019)
A new species of the flat mite genus Phyllotetranychus Sayed, 1938 (Acari: Trombidiformes: Tenuipalpidae), P. hadii sp. nov., is described based on the female, male and larval stages, collected from Washingtonia filifera (Arecaceae) in Iran.